PERENCANAAN PLTS OFF GRID DI DESA TOLONUO SELATAN KECAMATAN TOBELO UTARA KABUPATEN HALMAHERA UTARA - M. Yunus Hi. Abbas; Achmad P A. Sardju (Fakultas Teknik Universitas Khairun, 2022)
Electrical energy continues to increase along with the increasing number of human population and the more modern human lifestyle is one of the causes of energy consumption. The use of several electrical and electronic equipment to support the needs of society in today's modern era. Electrical energy is one of the main human needs in supporting people's daily lives, especially the upper middle class, therefore this need must be fulfilled and its utilization must be used efficiently. The PV mini-grid system requires a very large cost for a village scale from an economic point of view. Apart from the very large initial investment cost of Rp.2. 189.50 0.000,-, in general, if the infrastructure is improved, tourists will use higher electricity consumption, so that the area can improve the economy and village welfare. type of quantitative research. The quantitative aspect of this study is the collection of primary data regarding daily electrical energy needs in South Tolonuo Village using interviews and field observations. The daily energy requirement in South Tolonuo Village is 97 kWh/day or 97,000 Wh/day. To determine the peak power of PLTS, Global Horizontal Irradiance (GHI) data is required.